2021
DOI: 10.24200/sci.2021.56224.4610
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Effect of Ageing of Nano-Clay Modified Bitumen Using Atomic Force Microscopy

Abstract: This study investigates the effects of ageing simulation on the physical properties of nano-clay modified bitumens (NCMBs). Bitumen with penetration grade 60/70 is modified with 0, 2 and 4% nano-clay, and the consistency of the samples is characterized using the penetration, softening point, and viscosity tests before and after aging. Atomic force microscopy (AFM) is used to evaluate the surface roughness and tip deflection of the modified bitumens. The results of the consistency tests revealed that the incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(47 reference statements)
1
1
0
Order By: Relevance
“…It is observed from the FESEM micrograph that nano clay powders appear as grains located close to each other (Figure 2A). The appearance confirms the compatibility of nano clay particles with the HDPE matrix due to the consistency with the results presented in the study of Omar et al 16 Whereas CaCO 3 powders have an irregular shape with cleavages around the boundary of the particles and the HDPE (Figure 2B). Similar descriptions of CaCO 3 particles are given in the study of Minkowicz et al 17 CaCO 3 used together with the nano clay powder showed enhanced compatibility resulting in a high stress transfer from the matrix to the particles.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It is observed from the FESEM micrograph that nano clay powders appear as grains located close to each other (Figure 2A). The appearance confirms the compatibility of nano clay particles with the HDPE matrix due to the consistency with the results presented in the study of Omar et al 16 Whereas CaCO 3 powders have an irregular shape with cleavages around the boundary of the particles and the HDPE (Figure 2B). Similar descriptions of CaCO 3 particles are given in the study of Minkowicz et al 17 CaCO 3 used together with the nano clay powder showed enhanced compatibility resulting in a high stress transfer from the matrix to the particles.…”
Section: Resultssupporting
confidence: 90%
“…These deep grooves are identical in appearance and can be seen appearing at different locations on the surface profile (Figure 3C). 16 The excessive wear debris in the form transfer film of the non‐hybrid samples is the result of this exfoliation process on the surface of the wear track. Reflecting on the values of COF, the damage due to dry sliding is further avoided by the transfer film, which is manifested by the decrease in coefficient of friction (C.O.F.)…”
Section: Resultsmentioning
confidence: 99%
“…In another AFM study on adhesive surface characteristics, Lyne et al [97] concluded that a correlation existed between elastic modulus, adhesion forces and morphology of bitumen. In similar research, Omar et al [98] investigated the effect of nano-clay as a bitumen modifier and its effect on bitumen ageing behaviour using AFM. It was concluded that AFM has the ability to identify changes in bitumen fluidity, and different bee-like structures were recorded in different bitumen samples, even though they all had the same penetration value.…”
Section: Atomic Force Microscopy and Ageing Effects On Bitumenmentioning
confidence: 99%
“…Their findings indicate that the elevated transfer coefficient observed in the TiO 2 /Ag (Cr)/TiO 2 film resulted from a reduction in the thickness of the silver layers. This reduction led to diminished optical properties, surface plasma effects, and electron scattering, contributing to lower electrical resistance [22]. Fukuda et al employed Al/Ag/Al sandwich layers to enhance the thermal stability of silver films.…”
Section: Introductionmentioning
confidence: 99%